Peran Zakat Dan Wakaf Sebagai Alternatif Meningkatkan Kesejahteraan Masyarakat - Inne Risnaningsih (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2022)
This research aims to eksplained about zakat role and waqf especially money waqf as the alternative to improving social welfare. This research conducted is a descriptive qualitative study with the literature study. Based on research result state that to effect the zakat and waqf toward poored increasing to ower.given but on micro level,because that date limited and zakat and waqf contribution is small relative as more than Nasional economic. It is because still to integrated management zakat and waqf toward economic nasional polic.